Model Kepercayaan Konsumen Pada Situs E-Commerce di Indonesia Studi Kasus Kaskus.Co.Id - Wika Purbasari; Muh Sofi'i (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2018)
Today's world trading system has evolved to the online trade (elektronic commerce). There have been many people who purchase goods through e-commerce. It can be proved by Consumer Web Watch study which reported that 86% of internet users have switched to purchase traditionally into purchase online.Kaskus is ranked 251 in the world and becomes 7th most visited site in Indonesia. Therefore, it is needed for giving a prediction to find out what factors are shaping consumer confidence in Kaskus. Principle Component Analysis (PCA) is applied to select the irrelevant variables and to determine the magnitude of the correlation in order to group variables into the formed factors. This was done to provide information about any factors that shape consumers' confidence in Kaskus.